"I wouldn't even know where to start": unwanted pregnancy and abortion decision-making in Central Appalachia. Issue 52 (1st January 2018) - O'Donnell, Jenny; Goldberg, Alisa; Lieberman, Ellice; Betancourt, Theresa
Abstract: How rurality relates to women's abortion decision-making in the United States remains largely unexplored in existing literature. The present study relies on qualitative methods to analyze rural women's experiences related to pregnancy decision-making and pathways to abortion services in Central Appalachia. This analysis examines narratives from 31 participants who disclosed experiencing an unwanted pregnancy, including those who continued and terminated a pregnancy. Results suggest that women living in rural communities deal with unwanted pregnancy in three phases: (1) the simultaneous assessment of the acceptability of continuing the pregnancy and the acceptability of terminating the pregnancy, (2) deciding whether to seek services, and (3) navigating a pathway to service. Many participants who experience an unwanted pregnancy ultimately decide not to seek abortion services. When women living in rural communities assess their pregnancy as unacceptable but abortion services do not appear feasible to obtain, they adjust their emotional orientation towards continuing pregnancy, shifting the continuation of pregnancy to be an acceptable outcome. The framework developed via this analysis expands the binary constructs around abortion access – for example, decide to seek an abortion/decide not to seek an abortion, obtain abortion services/do not obtain abortion services – and critically captures the dynamic, often internal, calculations women make around unwanted pregnancy. It captures the experiences of rural women, a gap in the current literature.